Carbon Dioxide Reforming of Methane over Cobalt‐Nickel Bimetal‐Doped Ordered Mesoporous Alumina Catalysts with Advanced Catalytic Performances. Issue 15 (22nd June 2016) - Xu, Leilei; Wang, Fagen; Chen, Mindong; Zhang, Jian; Yuan, Kaidi; Wang, Liangjun; Wu, Kai; Xu, Guoqin; Chen, Wei
Abstract: Co‐Ni bimetal‐doped ordered mesoporous Al2 O3 composite oxides with different Co/(Co+Ni) ratios were designed and fabricated by a one‐pot evaporation‐induced self‐assembly method. The obtained materials, which had an ordered mesostructure and outstanding thermal stability, were investigated as catalysts for the CO2 reforming of CH4 . The effects of the Co/(Co+Ni) molar ratios and ordered mesostructure on the catalytic performances were investigated systematically. The ordered mesoporous Co‐Ni bimetallic catalysts exhibited both higher catalytic activities and better anticoke properties than the corresponding monometallic materials because of the Co‐Ni synergistic effect. Furthermore, the ordered mesostructure could promote the catalytic performances significantly by providing gaseous reactants with enough accessible metallic active centers and stabilizing the metallic nanoparticles through the confinement effect of the mesoporous framework. As a result, these mesoporous Co‐Ni bimetallic catalysts had more enhanced catalytic properties and anticoke ability than traditional supported catalysts toward the CO2 reforming of CH4, which promises a series of potential catalyst candidates. Abstract : Ordered mesoporous Co‐Ni bimetallic catalysts : A series of Co‐Ni bimetal‐doped ordered mesoporous Al2 O3 composite oxides with excellent textural properties and thermal stability is synthesized by a one‐pot evaporation‐induced self‐assembly method and utilized as catalysts for the CO2 reforming of CH4 . The Co‐Ni synergistic effect and ordered mesostructure play significant roles to improve the catalytic properties and coke resistance of the materials.